Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja pada Karyawan Minimarket ABC Kabupaten Toraja Utara - Arjuna Paembonan; Astriwati Biringkanae; Lisa Kurniasari Wibisono (CV. Ulil Albab Corp, 2024)
This research aims to determine the effect of work motivation (X1), work discipline (X2), on work productivity (Y). This research used a sampling technique using a saturated sampling method with a sample of 32 respondents. This research method uses quantitative research methods with the help of the SPSS 26.0 application as a tool for calculating the data that has been obtained. This research uses 3 variables. The independent variables are work motivation, work discipline, while the dependent variable is work productivity. The results of this research show that work motivation and work discipline simultaneously have a calculated F value (7.821) which is greater than F table (3.29). Partially, work motivation has no significant effect on work productivity, while work discipline has a significant effect on work productivity.